2020
DOI: 10.9795/bullgsj.71.313
|View full text |Cite
|
Sign up to set email alerts
|

Late Jurassic radiolarians from mudstone near the U–Pb-dated sandstone ofthe North Kitakami Belt in the northeastern Shimokita Peninsula, Tohoku, Japan

Abstract: In the northeastern Shimokita Peninsula, Aomori Prefecture, a Jurassic accretionary complex (AC) belonging to the North Kitakami Belt is distributed in three hilly areas of the Kuwabatayama, Katasakiyama and Omori. Although the AC in the Kuwabatayama area has been extensively studied and subdivided into the Late Jurassic Iwaya Unit and the Early Cretaceous Shitsukari Unit, those in the other areas are not fully understood except for a recent report of the detrital zircon U-Pb age from sandstone in the Omori ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Recently, as a result of surveys mainly in the Rikuchu-Seki District located north of our study area, Nakae et al (2021) proposed that the Seki Unit should be divided into two tectonostratigraphic units; the upper Kassenba Complex (coherent facies; chert, mudstone and sandstone) and the lower Seki Complex (coherent facies; chert and mudstone) Region (modified from Geological Survey of Japan, AIST, 2020). Age data of the accretionary complex are based on the compilation by Uchino and Suzuki (2020). Rads: radiolarian fossils.…”
Section: Geological Outlinementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, as a result of surveys mainly in the Rikuchu-Seki District located north of our study area, Nakae et al (2021) proposed that the Seki Unit should be divided into two tectonostratigraphic units; the upper Kassenba Complex (coherent facies; chert, mudstone and sandstone) and the lower Seki Complex (coherent facies; chert and mudstone) Region (modified from Geological Survey of Japan, AIST, 2020). Age data of the accretionary complex are based on the compilation by Uchino and Suzuki (2020). Rads: radiolarian fossils.…”
Section: Geological Outlinementioning
confidence: 99%
“…Fig.1 Geology of the basement rocks of northern TohokuRegion (modified from Geological Survey of Japan, AIST, 2020). Age data of the accretionary complex are based on the compilation byUchino and Suzuki (2020). Rads: radiolarian fossils.…”
mentioning
confidence: 99%
“…We studied pelagic deep-sea sedimentary rocks (mostly bedded chert) that belong to the Jurassic accretionary complex of the North Kitakami Belt (Ehiro et al, 2008). These sedimentary rocks were deposited in the Superocean Panthalassa (Figure 1A) then transported and accreted at the subduction zone along its western margin by plate motion during the Jurassic to earliest Cretaceous (Isozaki et al, 1990;Wakita and Metcalfe, 2005;Ehiro et al, 2008;Uchino and Suzuki, 2020).…”
Section: Geological Settingmentioning
confidence: 99%
“…This study revealed that the Takinosawa Unit distributed to the north of the Tsunatori Unit in the Nedamo Belt is an Early Triassic accretionary complex. Accretionary complexes in the North Kitakami Belt are considered to show a younging polarity of Early Jurassic to Early Cretaceous from southwest to northeast (Ehiro et al, 2008;Kojima et al, 2016;Suzuki et al, 2007;Uchino & Suzuki, 2020). Recently, a Late Triassic accretionary complex has been inferred on the basis of latest Triassic zircon-bearing and Middle-Late Triassic radiolarian-bearing tuffaceous mudstone (TfHi9 in Figure 2) in the south westernmost North Kitakami Belt, east of Morioka City (Uchino, 2017).…”
Section: Younging Polarity Of Accretionary Complexes In the Northern Kitakami Massifmentioning
confidence: 99%
“…High-P/T metamorphic rocks in both Southwest Japan and the Kitakami Massif might have formed in the same arc-trench system of the circum-Pacific orogenic belt (e.g., Tsujimori & Itaya, 1999). Based on lithological similarities, such as Megalodon-fossil-bearing Upper Triassic Suzuki et al (2007), Uchino and Suzuki (2020), and other studies referred to in these four papers limestone (Sano et al, 2009) and "Torinosu-type" Upper Jurassic limestone (e.g., Murata, 1962;Onuki, 1959), part of the Jurassic accretionary complexes in the Akka-Tanohata Subbelt of the North Kitakami Belt have been considered the Sanbosan Unit of the southern belt in the Chichibu Belt (e.g., Isozaki & Maruyama, 1991;Takahashi et al, 2016) (Figure 11). However, the Early Carboniferous Tsunatori Unit in the Nedamo Belt cannot be correlated with any geotectonic units in Southwest Japan.…”
Section: Correlation Of the Takinosawa Unitmentioning
confidence: 99%